Kentucky Bourbon Whiskey : An American Heritage - Veach, Michael R., 1958- (Book collections on Project MUSE., 2013)
On May 4, 1964, Congress designated bourbon as a distinctive product of the United States, and it remains the only spirit produced in this country to enjoy such protection. Its history stretches back almost to the founding of the nation and includes many colorful characters, both well known and obscure, from the hatchet-wielding prohibitionist Carry Nation to George Garvin Brown, who in 1872 created Old Forester, the first bourbon to be sold only by the bottle. Although obscured by myth, the history of bourbon reflects the history of our nation. Historian Michael R. Veach reveals the.